PENERAPAN TATA RUANG KANTOR PADA SUBBAGIAN ADMINISTRASI KEPEGAWAIAN KANTOR PUSAT PENGEMBANGAN SUMBER DAYA MANUSIA REGIONAL MAKASSAR - Syam, Shofiana (Saraq Opat: Jurnal Administrasi Publik, 2023)
This study aims to determine the Implementation of Office Spatial Planning in the Personnel Administration Subdivision of the Makassar Regional Development Headquarters and to find out the obstacles that arise from the application of the Office Spatial Principles. The type of research used is descriptive qualitative, namely describing or explaining the description of the situation and conditions obtained in the field, as well as interviews with staff at the Makassar Regional Center for Human Resource Development. After analyzing and discussing the problem, the authors come to the conclusion that the application of office layout in the Personnel Administration Subdivision of the Makassar Regional Human Resource Development Headquarters has not been carried out properly in accordance with the basic principles of office layout.